Cardiac Glycosides Activate the Tumor Suppressor and Viral Restriction Factor Promyelocytic Leukemia Protein (PML). - Snezana Milutinovic; Susanne Heynen-Genel; Elizabeth Chao; Antimone Dewing; Ricardo Solano; Loribelle Milan; Nikki Barron; Min He; Paul W Diaz; Shu-ichi Matsuzawa; John C Reed; Christian A Hassig (PLoS ONE)
Cardiac glycosides (CGs), inhibitors of Na+/K+-ATPase (NKA), used clinically to treat heart failure, have garnered recent attention as potential anti-cancer and anti-viral agents. A high-throughput phenotypic screen designed to identify modulators of promyelocytic leukemia protein (PML) nuclear body (NB) formation revealed the CG gitoxigenin as a potent activator of PML. We demonstrate that multiple structurally distinct CGs activate the formation of PML NBs and induce PML protein SUMOylation in an NKA-dependent fashion. CG effects on PML occur at the post-transcriptional level, mechanistically distinct from previously described PML activators and are mediated through signaling events downstream of NKA. Curiously, genomic deletion of PML in human cancer cells failed to abrogate the cytotoxic effects of CGs and other apoptotic stimuli such as ceramide and arsenic trioxide that were previously shown to function through PML in mice. These findings suggest that alternative pathways can compensate for PML loss to mediate apoptosis in response to CGs and other apoptotic stimuli.